The 1918 influenza epidemic's effects on sex differentials in mortality in the United States - Noymer, A.; Garenne, M.
tbls., gráfs.
pp. 565-581
Keywords: Mortalidad; Estados Unidos de America; Gripe; Epidemias; Tuberculosis; Promedio de Vida; Mortalidad Diferencial